2006
DOI: 10.2471/blt.05.024489
|View full text |Cite
|
Sign up to set email alerts
|

TB case-finding in southern Ethiopia

Abstract: Objective To ascertain whether case-finding through community outreach in a rural setting has an effect on case-notification rate, symptom duration, and treatment outcome of smear-positive tuberculosis (TB). Methods We randomly allocated 32 rural communities to intervention or control groups. In intervention communities, health workers from seven health centres held monthly diagnostic outreach clinics at which they obtained sputum samples for sputum microscopy from symptomatic TB suspects. In addition, trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 20 publications
0
22
2
Order By: Relevance
“…However, it is higher than the 197/100,000 py from Guinea-Bissau [54] and the 207/100,000 py from Southern Ethiopia [15]. Nonetheless, it is lower than the 311/100,000 py reported from Northern Ethiopia [11].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, it is higher than the 197/100,000 py from Guinea-Bissau [54] and the 207/100,000 py from Southern Ethiopia [15]. Nonetheless, it is lower than the 311/100,000 py reported from Northern Ethiopia [11].…”
Section: Discussionmentioning
confidence: 87%
“…The 214/100,000 py incidence rate of PTB+ cases in this study is similar to the 212/100,000 py reported from South Africa [ 53 ]. However, it is higher than the 197/100,000 py from Guinea-Bissau [ 54 ] and the 207/100,000 py from Southern Ethiopia [ 15 ]. Nonetheless, it is lower than the 311/100,000 py reported from Northern Ethiopia [ 11 ].…”
Section: Discussionmentioning
confidence: 98%
“…Randomizing both control and intervention areas adds strength to the results. 21 22 If randomization is not feasible, external factors should be systematically monitored and documented, and their effect on case notification in both evaluation and control populations estimated. Examples of such factors are the introduction or closure of other interventions affecting case notification, or political and natural events that impact health seeking or shape the effectiveness of screening efforts ( Box 1 ).…”
Section: A Pragmatic Framework For Monitoring and Evaluating Tb Case mentioning
confidence: 99%
“…Furthermore, research Pérez-Guerra, Zielinski-Gutierrez, Vargas-Torres and Clark (2009) concluded that suggested strategies to motivate citizen action included working with government agencies to address structural issues that increase mosquito populations, improve access to information on garbage collection and drainage through telephone hotlines, improve publications and information about dengue through media mass campaigns, and educating healthprofessionals. Shargie, Mørkve and Lindtjørn (2006) conducted a 4 days training program for public health workers on case detection, diagnostic procedures, outreach coordination, handling of sputum specimens, interview techniques, and record-keeping. Meanwhile, community health promoters held discussions with community leaders to set an appropriate monthly date for a diagnostic outreach clinic.…”
Section: Discussionmentioning
confidence: 99%